Effcacy of insecticides for the management of brinjal shoot and fruit borer, Leucinodes orbonalis - Niranjana et al, R F (Indian Journal of Plant Protection, 2018)
Field experiments were carried out during the seasons Rabi 2014-15 (October 2014 to January 2015) and summer 2015 (February to May 2015) at Alandurai, Thondamuthur, Coimbatore, Tamil Nadu, India to evaluate the effcacyof ten insecticides viz., imidacloprid 17.8% SL, thiacloprid 21.7% SC, thiodicarb 75% WP, chlorantraniliprole 18.5% SC, ﬂubendiamide 20 WG, emamectin benzoate 5 SG, diafenthiuron 50 WP, spinosad 2.5% SC, chlorpyrifos20% EC and dimethoate 30% EC along with untreated control against Leucinodes orbonalis on brinjal. The fndings revealed that the insecticide chlorantraniliprole 18.5% SC was effective and signifcantly superior to othertreatments in reducing the shoot and fruit infestation of L. orbonalis with least effect on natural enemies in brinjal felds. Besides, spinosad 2.5% SC and ﬂubendiamide 20 WG proved their effcacy next to chlorantraniliprole18.5% SC in controlling L. orbonalis incidence in brinjal.